2020
DOI: 10.1007/s40119-020-00188-1
|View full text |Cite
|
Sign up to set email alerts
|

Use, Persistence, Efficacy, and Safety of Apixaban in Patients with Non-Valvular Atrial Fibrillation in Unselected Patients in Germany. Results of the Prospective Apixaban in Atrial Fibrillation (APAF) Registry

Abstract: Introduction Apixaban has been shown to be superior to warfarin in patients with non-valvular atrial fibrillation in the randomized ARISTOTLE trial and its use is recommended in current guidelines. There are only scarce data about its use, efficacy, and safety in unselected patients in Germany. Methods and Results The APAF registry is a prospective non-interventional study enrolling 5015 patients with non-valvular atrial fibrillation. Of these, 1349 (26.9%) patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Although quality of coding renal impairment in claims data is known to be low, this still might indicate that a noticeable part could be underdosed with ld-DOAC. Previous studies showed that many patients (22 to 57%) with ld-DOAC do not meet the criteria for reduced dose [13,16,18,31]. Assumingly, prescribing a lower dose than recommended might be induced by the intention to protect the patient, as inadequate ld-DOAC is often prescribed in elderly patients at a higher risk for bleeding and stroke [16,18,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although quality of coding renal impairment in claims data is known to be low, this still might indicate that a noticeable part could be underdosed with ld-DOAC. Previous studies showed that many patients (22 to 57%) with ld-DOAC do not meet the criteria for reduced dose [13,16,18,31]. Assumingly, prescribing a lower dose than recommended might be induced by the intention to protect the patient, as inadequate ld-DOAC is often prescribed in elderly patients at a higher risk for bleeding and stroke [16,18,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that many patients (22 to 57%) with ld-DOAC do not meet the criteria for reduced dose [13,16,18,31]. Assumingly, prescribing a lower dose than recommended might be induced by the intention to protect the patient, as inadequate ld-DOAC is often prescribed in elderly patients at a higher risk for bleeding and stroke [16,18,31,32]. In the case of VKA therapy, patients at risk would possibly receive a close INR-monitoring to prevent overdosing or a dose targeted at the lower border of INR, as low-intensity VKA-therapy was shown to be as efficient and safer as standard VKA-therapy in a recent metaanalysis [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the mean CHA 2 DS 2 -VASc scores were 4.6, 4.2, and 4.2 for patients treated with apixaban, dabigatran, and rivaroxaban, respectively. In the XANTUS (Xarelto for Prevention of Stroke in Patients With Atrial Fibrillation) (registry the mean CHA 2 DS 2 -VASc score was 3.4 for rivaroxaban-treated patients [23], while in the APAF registry the mean CHA 2 DS 2 -VASc score was 3.8 for apixaban-treated patients [24].…”
Section: Discussionmentioning
confidence: 99%